La caída - Roa Limongi, Mateo (Pontificia Universidad Católica del Perú, 2024)
The family nucleus is usually considered as the fundamental cell of a society. A family has principles, values, norms, and beliefs that are transmitted from parents to children. There is no lack, within a family, of making memories and even comparisons that, on many occasions, lend themselves to sowing union or, failing that, discord. Based on this context, the purpose of this project is to problematize the recording devices through images extracted from the photographic album of a specific family nucleus. The twists of the narrative deal with the disease, the demolition of the house, the bodies of water, the Armero avalanche, and the germination of the trees. In this network of relationships, photography, as well as video, play a fundamental role. On the one hand, the photograph freezes several subjects preventing them from falling into the water, while the video shows the event from start to finish. The work advances in comparing the properties of the video with the reflection of those subjects who decide to jump into the water. A relevant fact of this narrative is the moment when the water turns into mud, in which the images are the reflection of the national catastrophe and the family tragedy. A transversal element of the project is the language around medicine as a resource to protect oneself from the destructive influence of ignorance, superstition, and charlatanism. The epilogue leads to consider the soils of tragedy as a substrate for the blossoming of a new becoming in the family album and an appropriate management to prevent and treat diseases.

El núcleo familiar suele ser considerado como la célula fundamental de una sociedad. Una familia cuenta con principios, valores, normas y creencias que son transmitidos de padres a hijos. No falta, en el seno de una familia, realizar rememoraciones e incluso comparaciones que, en muchas ocasiones, se prestan para sembrar la unión o, en su defecto, la discordia. Con esto en mente, el objetivo de este proyecto consiste en problematizar los dispositivos de registro a través de imágenes extraídas del álbum fotográfico en un contexto familiar específico. Los giros de la narrativa abordan la enfermedad, la demolición de la casa, los cuerpos de agua, la avalancha de Armero y la germinación de los árboles. En esta red de relaciones, la fotografía, así como el video, cumplen un papel primordial. Por un lado, la fotografía congela a varios sujetos evitando que caigan al agua, mientras que el video muestra el suceso de principio a fin. El trabajo avanza comparando las propiedades del video con el reflejo de aquellos sujetos que deciden lanzarse al agua. Un hecho relevante de esta narrativa lo constituye el momento en que el agua se transforma en lodo, en el cual las imágenes son el reflejo de la catástrofe nacional y la tragedia familiar. Un elemento transversal del proyecto lo constituye el lenguaje en torno a la medicina como un recurso para guardarse, al mismo tiempo, de la influencia destructiva de la ignorancia, de la superstición y de la charlatanería. El epílogo, lleva a considerar los suelos de la tragedia como sustrato para el florecimiento de un nuevo devenir en el álbum familiar y un manejo apropiado para precaver y tratar las enfermedades.
The fall
Keywords: Familia; Armero; Casa; Dispositivos de Registro; Árboles; Cuerpos de Agua; https://purl.org/pe-repo/ocde/ford#6.04.01